PENERAPAN REALISTIC MATHEMATICS EDUCATION (RME) DI SEKOLAH DASAR - Dyah Anungrat Herzamzam; Ilmi Noor Rahmad (Program Studi PGSD Universitas Flores, 2020)
The low learning outcomes about mathematics are the background of research problems. The purpose of this study was to improve the mathematics learning outcomes of multiplication material through the Realistic Mathematics Education (RME) learning model for grade III students in the even semester of the 2019/2020 school year. This research method is Classroom Action Research which follows the model of Kemmis and Taggart. This research includes 3 cycles where each cycle includes 4 stages, namely planning, implementing, observing and reflecting. The research time was from January to March 2020 with 30 students as research subjects, while the data were collected through tests, interviews and observations. The research results show that there is a significant increase in mathematics learning outcomes in class III. This is evidenced by the increase in the average result of the math test in each cycle, namely in cycle 1: 64.26 then cycle 2: 70.86 and cycle 3: 78.2. The results of researcher's observations in each cycle also increased, namely in cycle 1 = 2.44; cycle 2 = 2.88; cycle 3 = 3.89. Likewise, the results of student observations also increased, namely in cycle 1 = 2.4; cycle 2 = 3,2; cycle 3 = 4. And the results of the interviews conducted concluded that learning mathematics through the Realistic Mathematics Education (RME) learning model was fun for students. This study concluded that learning mathematics using the Realistic Mathematics Education (RME) learning model can improve student mathematics learning outcomes on multiplication material.